Exploring Subsurface Water Seasonal Trends: Musi River Command Area, India - Hussain, Mohammed Zakir (Research Advances in Environment, Geography and Earth Science Vol. 8, 2024)
The objective is to explore the seasonal trends in Musi River groundwater at various sampling stations in the Musi River command area. A total of ten parameters were analyzed of river groundwater during pre and post-monsoon in two years respectively 2020-21. The results were a drop in water quality with seasonal trends among the sites. The data have been compared with the health-based guidelines of the World Health Organization (WHO), increase in pollution load during the rainy season indicated the increase in organic matter in river water during the season due to an increase in anthropogenic interferences of the surrounding areas. Except for fluoride, every parameter in the data analysis displayed in Table 11 has a high standard deviation. This is proof of seasonal variation and wastewater discharge variation. According to Table 10's data analysis, there is a stronger association between post-monsoon This demonstrates how the monsoon water was added and how it seeped into the groundwater. The following tables, which show the findings, are corresponding to 12, 13, 14, and 15. According to WQI, the water is getting worse in quality. Seasonal changes and partially or fully treated industrial wastewater discharge are to blame for this.